SIMULATION OF REAL AND REACTIVE POWER FLOW ASSESSMENT WITH FACTS CONNECTED TO A SINGLE TRANSMISSION LINE - Prof. Mrs. Shrunkhala G. Khadilkar (International Journal of Innovations in Engineering Research and Technology, 2021)
Flexible alternating current transmission systems(FACTS) technologies opens up new opportunities for controlling power and enhancing the usable capacity of present as well as new upgraded lines. FACTS devices use power electronics components to improve system performance. This paper will discuss and demonstrate, how fixed capacitor thruster controlled reactor (FC-TCR) and static synchronous compensator (STATCOM), Unified power flow controller (UPFC) are applied to control transmission system dynamic performance for system disturbance and effectively regulate system voltage. SVC and Static synchronous compensator (STATCOM) is basically a shunt connected Static VAR generator whose output is adjusted to exchange capacitive or inductive current so as to maintain or control specific power variable;